Manejo de irrigação do melão cantalupensis no Semi-Árido - Gerhardt, Marcio Arlei (Universidade Federal Rural do Semi-Árido, 2007)
Currently, the meloeiro is one of the olerícolas of bigger economic and social expression for the Northeast Region of Brazil. The culture of the cantaloups does not provide only economic benefits, but also social benefits, therefore it guarantees about 40 a thousand jobs indirect right-handers and (BRAZIL, 2003). Ahead of this, the objective of this work was to evaluate the behavior of rendilhado cantaloups hybrids submitted the five blade of irrigation (70, 85, 100, 115 and 130% of the Kc), in the parameters of productivity and quality of the fruits. An experiment was lead in the period of June of 2006 the January of 2007, in the farm cantaloups Water, producer, located in the city of Quixeré (CE). In the evaluation of the experiment, the experimental delineation of casualizados blocks complete in subdivided parcels was used, with three repetitions. The first placed factor the parcels had been the five blades of irrigation (70% of ETO, 85% of ETO, 100% of ETO, 115% of ETO, 130% of the ETO) and placed subparcelas cantaloups had been the six cantaloups hybrids (type cantaloupe: Hy - Mark, Torreon e Cristobal and the gália type: AF 3360, Gallardo, Yupi). The evaluated characteristics had been: productivity, number of fruits, average weight of the fruit, variability of the size of the fruit, time of maturity, days the first mature fruit, Period of maduração: Number of days of the first flower to the first mature fruit, all up weight of fruit for plant, thickness of the pulp, diameter of the internal socket, firmness of the pulp, total soluble solid text. The harvest of the cantaloups after had a period of 9 days with beginning to the 62 days the plantation (DAP). Differences had occurred through the time where if it reaches the maximum value of sugar between the days 64 and 66DAP with 12,7 the 13,5 ºBrix, having a decrease of the text of in agreement sugar the increment of plates of irrigation. The handling of the irrigation in the preparation and conduction of the harvest of the Torreon cantaloups, implied in the reduction of the Kc, from 55 DAP of 0,7 for 0,53 making with that the volume of water offered to the 55 diminished of 26,7mm for 11,6, 12,5 and 11,6 mm to the 59, 63 and 67 DAP. The hídridos ones of cantaloups had presented similar productive behavior and superior texts of sugar 10o Brix
Irrigation management of melon cantalupensis in the Semi-Arid
Keywords: Melon; Irrigation coefficient of cultivation; Semi-Arid; Melão; Irrigação coeficiente de Cultivo; Semi-Árido; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA